Apuntes para una historiografía jurídica feminista - Costa Wegsman, Malena (2022)
This text was first published as a chapter in the book: Prado, Celia (ed.) and Josefa Ruiz Resa (dir.) (2020), Women and the Legal Professions, Madrid, Dykinson, pp. 307-317